2005
DOI: 10.1038/ni1289
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing regulatory T cell control of autoimmune responses in nonobese diabetic mice

Abstract: The in vivo mechanism of regulatory T cell (T(reg) cell) function in controlling autoimmunity remains controversial. Here we have used two-photon laser-scanning microscopy to analyze lymph node priming of diabetogenic T cells and to delineate the mechanisms of T(reg) cell control of autoimmunity in vivo. Islet antigen-specific CD4(+)CD25(-) T helper cells (T(H) cells) and T(reg) cells swarmed and arrested in the presence of autoantigens. These T(H) cell activities were progressively inhibited in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

55
674
6
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 710 publications
(740 citation statements)
references
References 41 publications
55
674
6
2
Order By: Relevance
“…Our current data provide experimental evidence that the immunoregulatory activity of naive-like Treg indeed requires CCR7 expression to traffic through LN, thus enabling inhibition of the priming phase of an immune response. Direct interactions between Treg and DC bearing autoantigens have recently been reported to precede inhibition of T cell activation [37]. Since mature DC also express CCR7 [20], it is tempting to speculate that CCR7 expression supports co-localization of both cell types within the antigen-draining LN; circumstances, where CCR7 expression on both T cells and DC is disabled, could additionally aggravate the functional defects.…”
Section: Discussionmentioning
confidence: 99%
“…Our current data provide experimental evidence that the immunoregulatory activity of naive-like Treg indeed requires CCR7 expression to traffic through LN, thus enabling inhibition of the priming phase of an immune response. Direct interactions between Treg and DC bearing autoantigens have recently been reported to precede inhibition of T cell activation [37]. Since mature DC also express CCR7 [20], it is tempting to speculate that CCR7 expression supports co-localization of both cell types within the antigen-draining LN; circumstances, where CCR7 expression on both T cells and DC is disabled, could additionally aggravate the functional defects.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood was obtained from patients with various subtypes of CLE (SCLE, DLE, LET) (n ϭ 12) as well as from normal healthy donors (n ϭ 18) and separated by Ficoll gradient centrifugation. The detection of Treg by analysis of CD4ϩ,CD25 high cells has produced conflicting results in patients with SLE (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)31,32). Therefore, we used a new intracellular staining method to directly visualize Foxp3ϩ Treg by flow cytometry, which was performed according to the manufacturer's protocol, as described previously (25).…”
Section: Methodsmentioning
confidence: 99%
“…Treg can suppress conventional T cells (Tcon) by direct cell contact in vitro (8), but down-modulation of dendritic cell (DC) function and secretion of inhibitory cytokines, such as interleukin-10 (IL-10) and transforming growth factor ␤ (TGF␤), might contribute to Treg function in vivo (10,11). A major unanswered question about Treg-mediated suppression concerns the location at which tolerance induction occurs in vivo.…”
mentioning
confidence: 99%
“…However, a few antigen-specific Tregs have been identified so far, most likely due to hitherto inadequate technical tools (e.g., MHC class II tetramer assays). Studies in mice have demonstrated that antigen-specific Tregs show a superior immunosuppressive activity as compared to nonspecific Tregs [81,82]. Wang et al were the first to isolate human tumor-associated antigen (TAA)-specific Tregs, in particular Tregs that were specific for the cancer/testis antigen LAGE1 among the TILs of melanoma patients [83].…”
Section: Specificity Of Tregsmentioning
confidence: 99%